Cancer-Associated Venous Thromboembolism: A Practical Review Beyond Low-Molecular-Weight Heparins - Smrke, Alannah; Gross, Peter L. (Frontiers in Medicine, 2017)
Patients with cancer are at significantly higher risk of developing, and dying from, venous thromboembolism (VTE). The CLOT trial demonstrated superiority of low-molecular-weight heparins (LMWH) over warfarin for recurrent VTE and established LMWH as the standard of care for cancer-associated VTE. However, with patients living longer with metastatic cancer, long-term injections are associated with significant cost and injection fatigue. Direct oral anticoagulants (DOACs) are an attractive alternative for treatment of cancer-associated VTE. Meta-analysis of subgroup data of patients with cancer from the large DOAC VTE trials and small non-randomized studies have found no difference in VTE recurrence or major bleeding. With this limited evidence, clinicians may decide to switch their patients who require long-term anticoagulation from LMWH to a DOAC. This requires careful consideration of the interplay between the patient’s cancer and treatment course, with their underlying comorbidities.